Improving Student Learning Outcomes in Islamic Education Learning through the Problem Based Learning Method at SD Negeri Bukit Baro - Subhiyah, Lili; Syamsiah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes through the Problem Based Learning method on the learning material 'My Ambition to Become a Pious Child' in class V of Bukit Baro State Elementary School, Montasik District, Aceh Besar Regency in the 2024/2025 Academic Year. This research is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were class V students of Bukit Baro State Elementary School, Montasik District, Aceh Besar Regency, with a total of 22 students involved in this study. The research data were obtained using test and observation techniques. The test was used to measure student learning outcomes before and after the action, while observation was used to analyze teacher and student learning activities during the learning process. The data analysis techniques used in this study were quantitative and qualitative descriptive analysis, by comparing student learning outcomes in each cycle and observing the increase in student involvement in the learning process. The results showed that the application of the Problem Based Learning method can improve student learning outcomes. This can be seen from the increase in the percentage of students' understanding of the teaching material, which was from 36% in cycle I, increasing to 55% in cycle II, and reaching 100% in cycle III. Thus, the use of the Problem Based Learning method can be used as an effective learning strategy in improving student learning outcomes, especially in Islamic Religious Education subjects. This method is also recommended to be applied in learning in elementary schools to increase student involvement and understanding of the teaching material.